Prolonged mantle residence of zircons xenocrysts from the western Eger rift. - Siebel, W.; Schmitt, A.; Danisik, Martin; Chen, F.; Meier, S.; Wei, S.; Eroglu, S. (Nature Publishing Group, Macmillan Publishers Ltd, 2009)
Zircon is a common mineral in continental crustal rocks. As it is not easily altered in processes such as erosion or transport, this mineral is often used in the reconstruction of geological processes such as the formation and evolution of the continents. Zircon can also survive under conditions of the Earth's mantle, and rare cases of zircons crystallizing in the mantle significantly before their entrainment into magma and eruption to the surface have been reported. Here we analyse the isotopic and trace element compositions of large zircons of gem quality from the Eger rift, Bohemian massif, and find that they are derived from the mantle.(U–Th)/He analyses suggest that the zircons as well as their host basalts erupted between 29 and 24 million years ago, but fragments from the same xenocrysts reveal U–Pb ages between 51 and 83 million years. We note a lack of older volcanism and of fragments from the lower crust, which suggests that crustal residence time before eruption is negligible and that most rock fragments found in similar basalts from adjacent volcanic fields equilibrated under mantle conditions. We conclude that a specific chemical environment in this part of the Earth's upper mantle allowed the zircons to remain intact for about 20–60 million years.